Some political-ideological notes on Teatro Oficina and its theatrical aesthetic (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This paper aims to offer a political-ideological inventory of the scenic practices incorporated by Teatro Oficina (SP) and its main animator, José Celso Martinez Corrêa, from 1968 to the mid-2000s. In the first part, a survey is made of the main analyses and criticisms directed at the São Paulo group, in ideological terms, over the course of its history. In the second part, based on a problematization of the use of nudity in the group's shows, we discuss the influences that explain this choice and its respective ideological repercussions. In the final section, by way of a conclusion, an attempt was made to round off the debate, with a view to establishing a synthesis that brings together the views set out above.
Keywords: oficina theatre; José Celso Martinez Corrêa; ideological criticism; history of Brazilian theatre; history of São Paulo theatre